Structure of the yeast ribonucleotide reductase Y2Y4 heterodimer - Voegtli, Walter C. (The National Academy of Sciences, 2001)
The R2 subunits of class I ribonucleotide reductases (RNRs) house a diferric-tyrosyl radical (Y·) cofactor essential for DNA synthesis. In yeast, there are two R2 proteins, Y2 and Y4. Although both Y2 and Y4 are homologous to R2s from other organisms, Y4 lacks three conserved iron-binding residues, and its exact function is unclear. Y4 is required for assembly of the diferric-Y· cofactor in Y2, and the two proteins can form both homodimeric and heterodimeric complexes. The Y2Y4 heterodimer was crystallized from a mixture of the two proteins, and its structure was determined to 2.8 Å resolution. Both Y2 and Y4 are completely α helical and resemble the mouse and Escherichia coli R2s in overall fold. Three α helices not observed in the mouse R2 structure are present at the Y2 N terminus, and one extra N-terminal helix is observed in Y4. In addition, one of the eight principal helices in both Y2 and Y4, αD, is shifted significantly from its position in mouse R2. The heterodimer interface is similar to the mouse R2 homodimer interface in size and interacting residues, but loop regions at the interface edges differ. A single metal ion, assigned as Zn(II), occupies the Fe2 position in the Y2 active site. Treatment of the crystals with Fe(II) results in difference electron density consistent with formation of a diiron center. No metal-binding site is observed in Y4. Instead, the residues in the active site region form a hydrogen-bonding network involving an arginine, two glutamic acids, and a water molecule.